Generating dermatopathology reports from gigapixel whole slide images with HistoGPT - Manuel Tran; Paul Schmidle; Ruifeng Ray Guo; Sophia J. Wagner; Valentin Koch; Valerio Lupperger; Brenna Novotny; Dennis H. Murphree; Heather D. Hardway; Marina D’Amato; Judith Lefkes; Daan J. Geijs; et al. (Nature Communications)
Abstract Histopathology is the reference standard for diagnosing the presence and nature of many diseases, including cancer. However, analyzing tissue samples under a microscope and summarizing the findings in a comprehensive pathology report is time-consuming, labor-intensive, and non-standardized. To address this problem, we present HistoGPT, a vision language model that generates pathology reports from a patient’s multiple full-resolution histology images. It is trained on 15,129 whole slide images from 6705 dermatology patients with corresponding pathology reports. The generated reports match the quality of human-written reports for common and homogeneous malignancies, as confirmed by natural language processing metrics and domain expert analysis. We evaluate HistoGPT in an international, multi-center clinical study and show that it can accurately predict tumor subtypes, tumor thickness, and tumor margins in a zero-shot fashion. Our model demonstrates the potential of artificial intelligence to assist pathologists in evaluating, reporting, and understanding routine dermatopathology cases.